Pengaruh Penerapan Problem Based Learning terhadap Hasil Belajar Siswa pada Subtema Lingkungan dan Manfaatnya di Sekolah Dasar Negeri Bojong Kabupaten Bogor Tahun Pembelajaran 2022/2023 - Ade Fauzi; Tatang Muhajang; Nur Hikmah (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to investigate the impact of using the Problem-Based Learning (PBL) model on the learning outcomes related to the environmental subtheme and its benefits among fifth-grade students. The research was conducted at Bojong State Elementary School, Bogor Regency, involving Class VA and Class VB during the second semester of the 2022/2023 academic year. The N-Gain calculation for the PBL model yielded a score of 70, indicating a high level of improvement, while the Control model resulted in an N-Gain score of 63, indicating a moderate level of improvement. Thus, the experimental group using the PBL model demonstrated higher N-Gain compared to the control group using the discovery learning model. Normality tests using the Liliefors test confirmed that both samples were normally distributed, as the sample values were smaller than the critical value (Ltable). The results of the homogeneity test showed that the data were homogeneous, as the Fcount value (1.05) was lower than the Ftable value (2.03). Hypothesis testing indicated that the tcount value (2.87) exceeded the ttable value (2.01), leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (Ha). Therefore, based on this research, it can be concluded that the application of Problem-Based Learning has a significant impact on the learning outcomes related to the environmental subtheme and its benefits.